The effect of the current realities of the fourth industrial revolution on the skills of management accountants: An exploratory study In the Iraqi business environment (Entrepreneurship Journal for Finance and Business, 2022)
The rapid developments in digital technologies have demonstrated different types of economic and social transformation called the Fourth Industrial Revolution (4IR), as these transformations expected to affect business models, the nature of services provided by management accountants, and their role in business organizations.The research discusses the possible effects of the realities of the Fourth Industrial Revolution on the skills of managerial accountants, assuming that there is a relationship between the data of the Fourth Industrial Revolution and the expected skills of managerial accountants in the Iraqi business environment. The research also aims to determine the type of skills required and the arrangement of those skills in light of the realities of the Fourth Industrial Revolution from the viewpoint of management accountants in the Iraqi business environment.            The research concluded with a set of conclusions that the fourth industrial revolution will create a technical disruption that leads to the decline of the traditional roles of management accountants and creates demand for new skills that require a different form of skill, and reflected in the rates of wages paid to management accountants. In addition to, in light of this the research recommends the need to qualify administrative accountants with technical qualifications that help them to deal with the realities of the Fourth Industrial Revolution.